How to prepare for the TOEIC test : - Lougheed, Lin (Trẻ, 2004)
The Test of English for International Communication is taken by students for whom English is their second language. It is required by many businesses and institutions in the English-speaking world when those students apply for positions. This new edition of Barron’s test prep package has been updated to reflect the most recent TOEIC exams. The illustrated manual presents six full-length model tests and a reading comprehension review. This special test prep package includes the manual along with four compact discs that present a thorough listening comprehension review. The CD program has been designed to coincide with listening comprehension material that is presented in the manual. The compact discs can also be purchased separately.